Cross-border Displacement: Prevent, Prepare or Adapt to? - Sepka,Monica (2017)
Despite the fact that some forecasts suggest that a large number of individuals could become displaced by 2050, the institutional and operational linkages between climate and cross-border displacement continues to be complex. While refugees and IDPs are treated according to specific treaties, the status of cross-border displacement as a result of disasters suffers from a normative gap and the linkages between disaster displacement, its drivers and risk reduction seems rather underrepresented in existing research. The purpose of this research is to investigate if cross-border displacement is adequately addressed in institutional and operational frameworks, and how transboundary and regional cooperation plays a role in mitigating displacement risk in the country of origin or within regions. This was approached by interviewing fourteen relevant actors, conducting a questionnaire and assessing literature through a triangulation of data sources. By following the structure of four research objectives, the policy approach and the risk reduction approach were investigated. The study concludes that several factors can be inhibiting for successfully mitigating displacement risk. It is recommended that the objectives of the policy approach and the risk reduction approach are assembled in a coextending manner and that there is a need for leadership and stakeholder mapping. In order to guide forced migration, developing global outlines and then tailor those to national and sub-national binding points are recommended. Furthermore, data collection that identifies and categorises drivers for displacement is recommended in order to reduce risks.
Keywords: Disaster Risk Management; Environment; Migration; Displacement; Drivers